2014
DOI: 10.1038/nrrheum.2014.20
|View full text |Cite
|
Sign up to set email alerts
|

The social (media) side to rheumatology

Abstract: A revolution is underway in the fields of education and health practice. Social media are now considered by the new generations of students, doctors and patients as a useful tool for learning and for doctor-doctor, doctor-patient and patient-patient communications. However, should we be excited by this revolution or afraid of it? Advantages and challenges of such new tools for medicine in general and rheumatology in particular are discussed in this Perspectives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 33 publications
(31 reference statements)
0
18
0
Order By: Relevance
“…Previously, traditional means of professional communication such as telephone calls, fax and post have been replaced by the emergence of quicker and more interactive online methods of communication 2. Aside from empowering participants to contribute content and develop online communities,3 4 SM platforms can be used to support clinically relevant discussions and information-sharing eliminating geographical barriers while bringing people closer together 5…”
Section: Introductionmentioning
confidence: 99%
“…Previously, traditional means of professional communication such as telephone calls, fax and post have been replaced by the emergence of quicker and more interactive online methods of communication 2. Aside from empowering participants to contribute content and develop online communities,3 4 SM platforms can be used to support clinically relevant discussions and information-sharing eliminating geographical barriers while bringing people closer together 5…”
Section: Introductionmentioning
confidence: 99%
“…However, radiologists cannot afford to ignore the importance of social media in a world where most of generation Y access social media multiple times per day. 3 Social media will be an important and integral part of the professional lives of tomorrow's generation of consultant radiologists; thus, we need to consider its influence and impact today.…”
Section: Resultsmentioning
confidence: 99%
“…3 This can include online forums, e.g., Doctors.net; microblogging platforms, e.g., Twitter; social networking sites, e.g., Facebook; and content communities such as Youtube. The idea of online professional networks is well established within business where members across the world use Linkedin to publicize their work, network with industry colleagues, and meet recruiters.…”
Section: What Are Social Media?mentioning
confidence: 99%
“…To date, there has been little research into the use of social networking sites for health by age group . While social media might improve access to self‐management tools and enable people with arthritis to choose how they interact , a published review concluded that research into social media and chronic disease management is still in its infancy . Recently, a systematic review and meta‐analysis found that social networking sites (including Facebook pages, health‐specific sites, and Twitter) were effective in improving health behaviors, although none of the included studies involved people with OA .…”
Section: Discussionmentioning
confidence: 99%